The contribution of the eco-pesantren model from a triple bottom line perspective at al-amien Prenduan Islamic Boarding School - Izzat Amini; Lala Olivia; Ach. Nurholis Majid (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose – The growing environmental crisis highlights the need for transformative educational models that foster sustainability across environmental, social, and economic domains. This study investigates the contribution of eco-pesantren practices at Al-Amien Prenduan Islamic Boarding School using the Triple Bottom Line (TBL) framework, which emphasizes environmental responsibility (planet), social welfare (people), and economic viability (profit). Method – This study employed a descriptive qualitative case study approach. Data were collected through participatory observation, in-depth interviews, and document analysis, and subsequently analyzed using the Triple Bottom Line (TBL) framework. Findings – The findings reveal that eco-pesantren practices at Al-Amien Prenduan Islamic Boarding School contribute substantially to all three dimensions of the Triple Bottom Line. In the social dimension (people), ecological citizenship is cultivated through the internalization of environmental values, active participation, and the integration of sustainability principles into educational activities, fostering collective environmental awareness and the development of ecological character and habitus. In the environmental dimension (planet), the pesantren implements systematic environmental management through greening initiatives and spatial planning, water conservation programs utilizing infiltration wells, and circular-based waste management practices. In the economic dimension (profit), the institution has established an integrated ecological value system that generates direct economic gains from waste processing, indirect benefits through improved operational efficiency, and intangible benefits, including enhanced institutional reputation and a more conducive learning environment. These findings suggest that the integration of the Triple Bottom Line framework into eco-pesantren practices not only promotes environmental sustainability but also strengthens social responsibility and economic resilience. The study highlights the importance of adopting a holistic and integrative approach to advancing sustainability within educational institutions.